Efficacy and safety of prolonged release budesonide granules in mesalazine‐refractory ulcerative colitis: A multi‐centre Phase IIa study (TOPICAL‐1). Issue 10 (12th January 2020) - Fellermann, Klaus; Schiefke, Ingolf; Rácz, István; Derova, Jelena; Jonaitis, Laimas; Wehrum, Sarah; Nacak, Tanju; Greinwald, Roland
Abstract : Background: In patients with mesalazine‐refractory ulcerative colitis, systemic corticosteroids are the treatment of choice. Objective: To evaluate the efficacy and safety of prolonged release budesonide granules for the induction of remission in patients with mesalazine‐refractory ulcerative colitis. Methods: Patients with mesalazine‐refractory ulcerative colitis discontinued mesalazine at baseline and received 9 mg prolonged release budesonide granules daily for 8 weeks in this open‐label, phase IIa study, followed by a 2‐week follow‐up phase wherein patients continued treatment on alternate days (EudraCT number 2014‐005635‐14; ClinicalTrials.gov identifier NCT02550418). The primary endpoint was clinical remission (Clinical Activity Index ≤4; stool frequency <18 per week; absence of rectal bleeding) at Week 8. Secondary endpoints included clinical, endoscopic and histological measures of disease at Week 8. A post hoc analysis assessed histo‐endoscopic mucosal healing. Treatment‐emergent adverse events and morning cortisol levels were assessed throughout the treatment and follow‐up phases. Results: A total of 61 patients were included in the intention‐to‐treat population; 50 were included in the follow‐up analysis set. Clinical remission was achieved in 29 patients (47.5%; 95% confidence interval: 34.6–60.7%) by Week 8. Mean stool and bloody stool frequency decreased significantly from 32.5 to 22.9 per week ( p <0.0001) and from 17.6 to 8.1 per week ( p <0.0001), respectively. Rates of mucosal healing, endoscopic remission and histological remission were 58.0%, 54.0% and 36.0%, respectively. Histo‐endoscopic mucosal healing was achieved by 34.0% of patients. Twenty‐four patients (39.3%) experienced treatment‐emergent adverse events, of which gastrointestinal disorders (16.4%) were the most common. Mean morning cortisol levels were not significantly suppressed by Week 8. Conclusions: Treatment with prolonged release budesonide granules for 8 weeks was associated with clinical, endoscopic and histological remission and demonstrated a favourable safety profile in patients with mesalazine‐refractory ulcerative colitis. These results warrant further investigation into the potential of prolonged release budesonide granules as an alternative treatment for this patient population.